Network Marketing Businesses and Chinese Ethnicity Immigrants in Australia. (31st May 2016) - Dai, Fu; Teo, Stephen T. T.; Wang, Karen Yuan
Abstract : This study adopts two theoretical perspectives, Social Cognitive Theory and Theory of Planned Behavior, to examine a model of network marketing business participation by Chinese immigrants in Australia. A structural equations modeling analysis showed that the social environment within a network marketing organization positively influences the self‐efficacy of Chinese network marketers and their desire to seek opportunities. These factors positively influence the actions undertaken by network marketers, and subsequently, impact positively on their performance outcome.